2020
DOI: 10.5937/mckg54-30496
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the influence of expanded hemodialysis on the rate of removal of middle molecular weight uremic toxins

Abstract: Objective. The aim of this study was to examine the effect of expanded hemodialysis on the degree of b2-microglobulin removal. Methods. Sixteen patients treated with extended MCO hemodialysis were examined. The main parameter for assessing the efficiency of removal of uremic toxins of middle molecular weight is the concentration of b2-microglobulin in the serum before and after a single session of extended MCO hemodialysis. The following were used for statistical analysis: Kolmogorov-Smirnov test, Student's T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…To prevent the development of complications of long-term hemodialysis treatment, post-dilution OL-HDF should enable RR-β2M of 80% (RR-β2M ≥ 80%) and RR-α1M of 35% (RR-α1M ≥ 35%) [35]. The results of the research done so far have shown that during a single session of high-flux "high-flux" hemodialysis RR-β2M is 50-60%, in extended hemodialysis ("medium cut-off" dialysis membrane) 70%, and in high-volume Vconv ≥ 22 liters/session) post-dilution OL-HDF 80-85% (RR-β2M ≥ 80%) [36], [37], [38]. In patients treated with postdilution OL-HDF with asymmetric triacetate cellulose dialysis membrane, at a blood flow rate of Qb = 400 mL/min, volume substitution -Vsubs = 24 liters/session and total convective volume -Vconv = 27.4 ± 3.4, RR-β2M was 79.3 ± 4.7%, and albumin loss during a single postdilution OL-HDF session about 500 mg (384.8-596.7 mg/4 h) [39].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the development of complications of long-term hemodialysis treatment, post-dilution OL-HDF should enable RR-β2M of 80% (RR-β2M ≥ 80%) and RR-α1M of 35% (RR-α1M ≥ 35%) [35]. The results of the research done so far have shown that during a single session of high-flux "high-flux" hemodialysis RR-β2M is 50-60%, in extended hemodialysis ("medium cut-off" dialysis membrane) 70%, and in high-volume Vconv ≥ 22 liters/session) post-dilution OL-HDF 80-85% (RR-β2M ≥ 80%) [36], [37], [38]. In patients treated with postdilution OL-HDF with asymmetric triacetate cellulose dialysis membrane, at a blood flow rate of Qb = 400 mL/min, volume substitution -Vsubs = 24 liters/session and total convective volume -Vconv = 27.4 ± 3.4, RR-β2M was 79.3 ± 4.7%, and albumin loss during a single postdilution OL-HDF session about 500 mg (384.8-596.7 mg/4 h) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Ovi uremijski toksini se efikasno uklanjaju konvencionalnom visokopropusnom hemodijalizom (0,5-20 kDa), postdilucionom online hemodijafiltracijom (0,5-60 kDa) i proširenom hemodijalizom -ED (0,5-60 kDa) (engl. Expanded Dialysis) (3,4). U uremijske toksine srednje molekulske mase spadaju proteini (β2-mikroglobulin), prozapaljenski citokini (interleukin-1β, interleukin-6, interleukin-18, faktor nekroze tumora alfa -TNF), proteini zapaljenja (pentraxin-3, YKL-40) i adipokini (leptin) (4).…”
Section: Uvodunclassified